2015
DOI: 10.5194/amt-8-5213-2015
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength light-scattering technique for selective detection of volcanic ash particles in the presence of water droplets

Abstract: Abstract.A new method is presented in this paper which analyses the scattered light of individual aerosol particles simultaneously at two different wavelengths in order to retrieve information on the particle type. We show that dust-like particles, such as volcanic ash, can be unambiguously discriminated from water droplets on a single-particle level. As a future application of this method, the detection of volcanic ash particles should be possible in a humid atmosphere in the presence of cloud droplets. The c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Scattering matrices for a number of typical atmospheric particulates including anthropogenic cement dust, natural dust (loess, desert sand, and volcanic ash), smolder smoke, soot, and water droplets are selected to discuss their application in identification methods for different kinds of particles (Bond & Bergstrom, ; Jurányi et al, ; Keller et al, ; Muñoz et al, ; Volten et al, ; Zhang et al, ). Soot particles were generated by burning of n‐heptane, while smolder smoke was emitted by nonflaming combustion of cotton (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scattering matrices for a number of typical atmospheric particulates including anthropogenic cement dust, natural dust (loess, desert sand, and volcanic ash), smolder smoke, soot, and water droplets are selected to discuss their application in identification methods for different kinds of particles (Bond & Bergstrom, ; Jurányi et al, ; Keller et al, ; Muñoz et al, ; Volten et al, ; Zhang et al, ). Soot particles were generated by burning of n‐heptane, while smolder smoke was emitted by nonflaming combustion of cotton (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Journal of Geophysical Research: Atmospheres discuss their application in identification methods for different kinds of particles (Bond & Bergstrom, 2006;Jurányi et al, 2015;Keller et al, 2006;Muñoz et al, 2007;Volten et al, 2001;Zhang et al, 2011). Soot particles were generated by burning of n-heptane, while smolder smoke was emitted by nonflaming combustion of cotton (Zhang et al, 2011).…”
Section: Discrimination Of Representative Atmospheric Particulatesmentioning
confidence: 99%
“…Sensor bekerja pada tegangan 5 V dan arus maksimum 120 mA serta telah dilengkapi dengan internal microcontroller unit (MCU), sehingga sensor ini dapat langsung melakukan komunikasi secara serial dengan MCU lainnya. Deteksi PM2.5 menggunakan prinsip hamburan cahaya untuk mengukur konsentrasi partikulat di udara, dimana hamburan tersebut bergantung dari ukuran, bentuk, indeks bias, dan sudut hamburan partikel, serta panjang gelombang dari laser (11) . Selain itu, pada lingkungan yang lembap, butiran-butiran uap air menempel pada partikulat di udara mengakibatkan akurasi sensor menjadi berkurang (12) .…”
Section: Alat Ukur Pm25 Dan Co2 Berbasis Low-cost Sensorunclassified
“…The CIP was not used for this study because it is unable to resolve the morphology of sub-75 μm particles, while a depolarization module in the CAS-POL allows for classification of particle morphologies and composition. [3033] NIOSH calibration experiments of the CAS-POL using size-selected coal dust demonstrated that the CAS-POL was capable of sizing coal dust particles by analyzing forward light-scattering measurements with T-matrix (sub-1.5 μm) and ray tracing with diffraction on facets (RTDF) (1.5–75 μm) theories for irregular particles. [34] While the coal dust calibration tests focused only on the use of forward scattered light to estimate particle size, the current study also analyzes the backscattered and polarized light to classify particles according to shape and composition, as both coal dust and water droplets are present during each knockdown test.…”
Section: Introductionmentioning
confidence: 99%